Professional profile of Latin American dentist. First part - Villavicencio, Judy (Revista Estomatología, 2015)
The training of dentistry professionals must ensure the development of scientific knowledge and technical skills without losing sight of training aspects such as the harmonious development of all dimensions of the individual involving ethical, cultural, social and humanistic elements that lead to training of men and women of good required for the progressive consolidation of a professional in dentistry (1,2). We must assume the training of professionals in dentistry from an integral point of view assuming the individual as a whole person, as a whole, where the existence of multiple human dimensions is recognized in constant interrelation, in permanent unfolding, present always in all areas of the existence (3,4).The educational processes in education allow to carry out processes of transformation and reproduction (5); allowing everyone, without exception, to fructify talents and creative abilities, which implies that each one can take responsibility for himself and carry out his personal project, in other words, the commitment to optimize the individual's capacities to guarantee the successful construction of a project of personal life and of a project of society that allows to respond in an appropriate way to the needs and expectations of the group to which it belongs. Four basic pillars of education are defined, which can be considered at the same time as pillars for the development of integral formation, from several dimensions: knowledge (learning to know), praxis (learning to do), ethics (learning to being) and the relationship with others (learning to live together), elements that coincide fully with the concepts proposed by other authors as philosophical support and operational framework for the materialization of the 'integral formation' in higher education.